Zero till in wheat from the gender perspective in Nepal - Sapkota, Sudha; Shrestha, Shukra Raj; Adhikari, Surya Prasad; Jha, Sanjeet Kumar; Gairhe, Samaya (Journal of Agriculture and Natural Resources, 2021)
Different tillage practices such as zero-till direct-seeded rice (ZTDSR), zero-till maize (ZTM), and zero-till wheat (ZTW) were implemented in the farmer's field of Sunsari district were evaluated. However, the focus was on ZTW because of high its competitiveness with cheaper wheat from abroad. Focus Group Discussion (FGD), Famers households keeping records, field monitoring, key informant interviews were the primary source of data whereas literature and desktop review were done for secondary data. Zero till wheat operation scale out of the machine use had been increased, by 61.25% out of 109.63ha land in Bhokraha and 66.49 % out of 55.3ha of land in Kaptangunj. Whereas, a new node Chitaha was established with the initiation of non-respondent farmer's where the area occupied 26ha in the year of 2019 respectively as compared to the base year that of 2014. Yield advantage was not much higher with ZTW, the additional benefit of almost 34% over conventional till wheat (CTW) was sufficient enough for the farmers to decide to adopt zero tillage technology. Farmers perceived about 17% saving in seed requirement, 13% saving in irrigation amount and time, and 44% saving in total labor cost with ZTW to make it more profitable as compared to CTW. Among different methods of extension, farmers’ field day with 63% and field trial with 48% with women's participation shows the most effective method to create awareness. Although the percentage of the working hour for the female worker is higher the number of the total hour has been decreased for both the man and women and the total 303.64hr/ha has been saved.